Multi-objective robust optimization design of a front-end underframe structure for a high-speed train. Issue 5 (4th May 2019) - Peng, Yong; Hou, Lin; Che, Quanwei; Xu, Ping; Li, Fan
ABSTRACT: A multi-objective robust design optimization of a front-end underframe structure for application in high-speed trains is proposed and the structural parameter uncertainty is considered. A finite element model of the structure is developed and verified by dynamic impact experiments. The sensitivity analysis demonstrates that the thicknesses of the centre sill have significant influences on structural crushing behaviours. The specific energy absorption and the initial peak crushing force ( Fp ) are taken as optimization objectives. Compared with the baseline structure, the 6-sigma robust design shows that the Fp and the structural mass are reduced by 54.86% and 13.06%, respectively, and the robust optimum is more reliable. The 6-sigma robust optimal solution has an efficient energy-absorbing capacity while satisfying the design constraint. Thus, 6-sigma robust optimization can be applied for high-speed trains.